Next generation sequencing of transcribed genes in ruminant γδ T cell populations. (September 2022) - Gillespie, Alexandria; Loonie, Kathleen; Zhang, Fengqiu; Prendergast, James; Connelley, Timothy; Baldwin, Cynthia L.
Abstract: Bovine γδ T cells are distinguished by expression of WC1, hybrid pattern recognition receptors and co-receptors to the T cell receptor (TCR), or their absence. WC1 molecules bind pathogens and the ability of γδ T cells to respond to pathogens largely correlates with their expression of particular WC1 genes. Following activation, the TCR and WC1 molecules co-localize and knocking down WC1 abrogates the ability of WC1-expressing γδ T cells to respond to antigen. It is known that these two major populations, WC1 + and WC1 -, differ in their TCR gene expression and previous studies showed other differences using semi-quantitative RT-PCR and serial analysis of gene expression. Differences in genes expressed would influence the functional outcome when WC1 + vs. WC1 - γδ T cells respond to pathogens. To identify unique aspects of their transcriptome, here we performed RNA-Seq of flow cytometrically sorted bovine WC1 + and WC1 - γδ T cells and compared them to all mononuclear cells in blood. The greatest differences in gene expression were found between γδ T cells and other mononuclear cells and included those involved in lymphocyte activation and effector processes. Only minor differences occurred between ex vivo WC1 + vs. WC1 - γδ T cells with those gene products being involved in cell adhesion and chemotaxis. After culturing cells from primed animals with Leptospira antigens major difference in the transcriptome was evident, with over 600 genes significantly differentially expressed including those focused on cytokine signaling. Unexpectedly, antigen-responding and non-responding populations of WC1 + γδ T cells had few differences in their transcriptomes outside of cytotoxic factors although they had more WC1–1, WC1–2 and WC1–13 transcripts. Through differential gene expression we were able to define properties of ex vivo and stimulated WC1 + cells which will be useful in understanding their functional biology. Graphical Abstract: ga1 Highlights: Major differences in gene expression occur between γδ T cells and other lymphocytes. Cell adhesion and chemotaxis gene transcription differs for WC1 + and WC1 - γδ T cells. Culture with antigen results in increased transcription of cytokine signaling genes. Antigen-responding WC1 + γδ T cells increase transcription of cytotoxic genes. WC1 + γδ T cells that divide in culture with antigen transcribe more WC1-1, 2 and 13.